Dog Days : Diary of a Wimpy Kid #4 - Bowers, David; Gordon, Zachary, 1998-; Bostick, Devon, 1991-; Harris, Rachael, 1968-; Shearmur, Edward; Kinney, Jeff (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2012)
When school ends for the summer, Greg's vacation doesn't go as he had planned.
Originally released as a motion picture in 2012.
Sequel to "Diary of a wimpy kid, Rodrick rules" (2011).
Based on the books by Jeff Kinney.
Features: audio commentary, deleted scenes with optional commentary, Class clown animated short, gag reel, theatrical trailer.
Camera, Anthony B. Richmond ; editor, Troy Takaki ; music, Edward Shearmur.
Zachary Gordon, Devon Bostick, Rachael Harris, Robert Capron, Steve Zahn, Peyton List, Conor Fielding, Owen Fielding, Grayson Russell, Karan Brar, Melissa Roxburgh.
Keywords: Kinney, Jeff -- Film adaptations; Middle school students -- Drama; Summer -- Drama; Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films; Comedy films